Spiritual education development model - Rohana Hamzah; Kamarudzaman Md Isa; Roziah Mohd. Janor (Faculty of Education, Universiti Kebangsaan Malaysia, 2010)
Developing and producing a holistic individual has been a major concern to Malaysian education system. Therefore, Malaysia education system was formed based on its mission to produce a balance and a holistic individual from physical, emotion, spiritual and intellectual potential based on a firm belief in and devotion to God. However, there was a gap between the current practice in education and the Malaysia’s education philosophy especially in the spiritual development domain. Meanwhile, self development from spiritual potential is the basic needs of every human being because it motivates good human behaviour and how they respond to the environment. Since, man is a combination of the soul and the body, man also carries dual tendencies which are tendencies to become good (motivate by the rational soul) and bad (motivate by the animal soul). Therefore, spiritual development process is about a continuous exercise of sub-ordination the animal soul to enslave itself in submission to the power of the rational soul. Therefore, the purpose of this study is to explore the philosophy behind self-development from spiritual domain and develop the conceptual model for spiritual development process.